Daily otolith growth and ontogenetic geochemical signatures of age-0 anchovy (Engraulis encrasicolus) in the Gulf of Cádiz (SW Spain). - CATALÁN, I. A.; PÉREZ-MAYOL, S.; ÁLVAREZ, I.; RUIZ, J.; PALMER, M.; BALDÓ, F.; PELIZ, Á.; MORALES-NIN, B. (Mediterranean Marine Science, 2014)
<!--[if gte mso 9]> <![endif]--> The European anchovy fishery in the Gulf of Cádiz (ICES Division IXa South) is largely influenced by age-0 individuals. Knowledge of young of the year growth dynamics is crucial for management, yet data on daily growth are lacking in the area. Linking growth patterns to the environment requires information on habitat occupancy through ontogeny of the fish that reach the fishery, as anchovy use different areas of the Gulf and the Guadalquivir Estuary through development. We describe the growth dynamics of age-0 anchovy through otolith microstructure analysis, and couple these data with data on microchemical signals in the otoliths to shed light into habitat use and growth dynamics in the area. Age-0 anchovy captured in September, 2011 in the Gulf ranged from 3 to 6 months old for similar sizes, with average growth rates varying twofold. Individual non-linear growth curves showed that maximum otolith growth was positively correlated with the date of spawning, which in turn was negatively correlated with the time to reach maximum growth. There was no correlation between growth parameters and body length or condition (Fulton K) at capture. The strontium:calcium (Sr/Ca) and magnesium:calcium (Mg/Ca) ratios were significantly lower at the edge of the otolith (approximately the age of capture) than at ages corresponding to larval and early juveniles (<60 days old), but values fell within typical estuarine-dwelling species. The barium:calcium ratio (Ba/Ca) increased significantly in the edge of the otolith, which possibly resulted from residency in highly productive coastal waters or from ontogenetic effects. The variance in otolith elemental ratios was larger at otolith back-calculated ages around 50 days old, age which coincides with the presumed closer dependence of estuarine waters. Our data are a first step towards understanding the contribution of the estuarine system to the fishery of anchovy in the Gulf. The limitations of the approach and future steps are discussed. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabla normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->